The characteristics of open cavity flow with a length to depth ratio of 4 - Pey, Yin Yin (2015)
The objective of this study is to characterize the flow behavior of an internal cavity of L/D=4, with its shear layer separated from a thick boundary layer at a free stream velocity of 15m/s. The study includes examining the cavity surface pressure and the associated flow structures. Pressure measurements were acquired from the cavity walls and the associated internal flow structures were studied using Particle Image Velocimetry (PIV). Several data processing techniques to study the flow structures were performed on the PIV data. These include time averaging quantities: velocities, vorticity and spatial correlation. In order to estimate the dynamics of the flow, the Proper Orthogonal Decomposition (POD) was applied to 900 independent PIV acquired velocities data set. The cavity wall surface pressure distribution indicated an open flow structure and was consistent with the mean velocity measurements which indicted a large re-circulating region within the cavity. Shear layer velocity profiles across the cavity revealed self-similarity beyond a distance of x/L=0.3. The shear layer growth rate of dθ/dx=0.031 was close to the entrainment rate of a turbulent mixing layer, dθ/dx=0.035. Two point spatial correlation coefficients of velocity fluctuations revealed a distinct pattern of alternating regions of positive and negative coefficient values, indicating the presence of organized coherent structures within the cavity. The modes one and two of the POD extracted structures indicated a flow structure of the closed cavity type. Mode three indicated the possibility of a large structure ejecting from the aft of the cavity. Keywords: open cavity, coherent structures, proper orthogonal decomposition, particle image velocimetry, spatial correlation, self-similarity, recirculation.